Modelling of Wireless Power Transmission - Abbas, SK; Swaroop, P.Jyothi; Priyanka, M. Swathi; Dinesh, R (International Journal of Computer Sciences and Engineering, 2019)
In this paper wireless power transmission (WPT) technique has been projected for transmitting the power in the electrical system.Transmission of electrical energy from source to load for a distance without any conducting wires or cables is called as wireless power transmission. In this paper renewable energy (electrical power is generated from solar panel) has been used as a source for the proposed technique. Then the generated electrical power is fed to DC-DC converter, hence the voltage is increased. After that the increased voltage has been fed to class E power amplifier. The output of class E amplifier i.e., 90V, 13.56 MHz is transmitted through transmitter to the receiver. One of the Near-field wireless power transfer techniques is opted i.e., (Magnetic resonance coupling). Magnetic Resonance coupling technique has been utilised for the transmission of power between transmitter and receiver. Then the Power from receiver has been fed to the rectifier circuit & converted into DC voltage around 75.6 V from that it has been given to DC load.